2006
DOI: 10.1111/j.1467-7687.2006.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain and cognitive‐behavioural development after asphyxia at term birth

Abstract: Perinatal asphyxia occurs in approximately 1-6 per 1000 live full-term births. Different patterns of brain damage can result, though the relation of these patterns to long-term cognitive-behavioural outcome remains under investigation. The hippocampus is one brain region that can be damaged (typically not in isolation), and this site of damage has been implicated in two different long-term outcomes, cognitive memory impairment and the psychiatric disorder schizophrenia. Factors in addition to the acute episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 86 publications
6
94
1
11
Order By: Relevance
“…The lack of reports of amygdala gray matter reductions in previous studies might be accounted for by the statistical threshold applied and/or the fact that apart from hippocampal formation, other medio-temporal lobe regions did not undergo rigorous volumetric quantifications Rosenbaum et al, 2011). In line with other studies showing damage to thalamic areas after episodes of (perinatal) hypoxia (Jacob and Pyrkosch, 1951;Voit et al, 1987;Markowitsch et al, 1997;Cowan et al, 2003;Macey et al, 2005;de Haan et al, 2006), we identified indices of reductions in gray matter density in thalamus, namely in the pulvinar, when we applied a less conservative statistical threshold (p < 0.001, uncorrected).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The lack of reports of amygdala gray matter reductions in previous studies might be accounted for by the statistical threshold applied and/or the fact that apart from hippocampal formation, other medio-temporal lobe regions did not undergo rigorous volumetric quantifications Rosenbaum et al, 2011). In line with other studies showing damage to thalamic areas after episodes of (perinatal) hypoxia (Jacob and Pyrkosch, 1951;Voit et al, 1987;Markowitsch et al, 1997;Cowan et al, 2003;Macey et al, 2005;de Haan et al, 2006), we identified indices of reductions in gray matter density in thalamus, namely in the pulvinar, when we applied a less conservative statistical threshold (p < 0.001, uncorrected).…”
Section: Discussionsupporting
confidence: 63%
“…However, the reported difficulties were milder than the ones experienced by ML. Although postulated, a connection between the basal ganglia (and thalamic) damage and motor impairment in cases of developmental amnesia remained unclear (Gadian et al, 2000;Vargha-Khadem et al, 2003;de Haan et al, 2006).…”
Section: Case Reportmentioning
confidence: 99%
“…Neonatal encephalopathy due to perinatal asphyxia or hypoxia-ischemia (HI) is an important cause of mortality in the neonatal period and is associated with high morbidity, mainly characterized by neurological deficits such as cerebral palsy, seizures, and sensory and cognitive limitations [1,2,3,4,5]. The prevalence of neonatal HI is about 2-6 per 1,000 live term births in Western countries [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a complex syndrome, with various clinical manifestations, from minimal serum creatinine increases to renal failure with anuria. [1][2][3][4][5] Serum creatinine is a biomarker commonly used to diagnose AKI. However, creatinine examination is not particularly sensitive or specific for diagnosing AKI, as other non-renal factors regulate creatinine, distribution volume, and creatinine excretion.…”
Section: Resultsmentioning
confidence: 99%